Advertisements - Connolly, Sean, 1956- (Mankato, Minn. : Smart Apple Media, 2010)
"Discusses the history of advertising and how businesses use advertising to targets consumers today, including print ads, TV ads, Internet ads, and viral marketing"--Provided by publisher.
The power of persuasion -- The language of advertising -- A campaign begins -- Releasing the message -- New and improved -- Blurred boundaries -- Targeting youth -- Going too far? -- Advertising watchdogs -- The final analysis -- The shape of the future.
Includes bibliographical references (p. 45) and index.
Keywords: Advertising -- Juvenile literature; Advertising and children -- Juvenile literature; Young consumers -- Juvenile literature